Fiscal decentralization in Buddhist economics: An interactive analysis from Lumbini - Bhusal, Indra Prasad (Research Nepal Journal of Development Studies, 2018)
The main objective of the article is to identify the basic elements of Buddhists Economics applicable to fiscal decentralization. The study reviews the Buddhists Economics and Fiscal Decentralization from global perspective. Fiscal decentralization is the process to deliver the power and resources to the grass root level of governance. If the governing body is able to impose the Buddha’s ideology in the policy, certainly resource allocation conflict will be minimized. Methodologically the researcher has conducted interaction programs among Buddhists economists, scholars and academicians available in Lumbini– the birth place of Buddha. The author has analyzed the facts matching with literature review and focused group discussion in Lumbini. The study has identified elements of fiscal decentralization from Buddhist Economics. These elements can be a guideline for noble scholars, academicians, researchers and policy makers of fiscal decentralization from Buddhists economics. Research Nepal Journal of Development Studies Vol.1(1) 2018 32-41